Unmet needs across Europe: Disclosing knowledge beyond the ordinary measure - Ramos, Luís Filipe Gens Moura (2019)
Unmet healthcare needs (or foregone healthcare) is a widely used intermediate indicator to evaluate healthcare systems attainment since it relates to health outcomes, financial risk protection, improved efficiency and responsiveness to the individuals' legitimate expectations. This paper discusses the ordinary measure of this indicator used so far, prevalence of unmet needs in the whole population, based on the level of healthcare needs among the population. The prevalence of needs and the prevalence of unmet needs among those in need are key aspects that have not yet been fully explored when it comes to foregone healthcare. We break down the ordinary measure into prevalence of needs and prevalence of unmet needs among those in need based on data taken from the European Social Survey 2014. Afterwards, we analyse these different measures in a cross-country perspective. We also discuss the link between them and the implicit relative assessment of healthcare systems considering the whole population and the sub-group of the population aged 65 or more. Comparisons across countries show different attainment levels unveiling varying challenges across European countries, depending on the combination of levels of need and levels of unmet needs for those in need.